2014
DOI: 10.1039/c3tc32049a
|View full text |Cite
|
Sign up to set email alerts
|

Cation exchange synthesis and optoelectronic properties of type II CdTe–Cu2−xTe nano-heterostructures

Abstract: interaction between the CdTe exciton and the Cu 2Àx Te plasmon. This lack of interaction may be due to the low spectral overlap between exciton and plasmon, but also to localization effects in the vacancydoped sub-unit. The electronic interaction between both sub-units was evaluated with pump-probe spectroscopy by assessing the relaxation dynamics of the excitonic transition. In particular, the CdTe exciton decays faster in the presence of the Cu 2Àx Te sub-unit, and the decay gets faster with increasing its l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 97 publications
(167 reference statements)
2
25
0
Order By: Relevance
“…Since the wurtzite CdS and orthorhombic Cu 2 S share similar anion sublattice, the lattice volume only decreases by 8% when CdS was converted to Cu 2 S, and therefore, the morphology and size of nanorods were well preserved after the cation exchange. Similar structures have been obtained in CdTe/Cu 2-x Te 44 and CdSe/ PbSe [99] systems.…”
Section: D Linear Heterostructuressupporting
confidence: 83%
“…Since the wurtzite CdS and orthorhombic Cu 2 S share similar anion sublattice, the lattice volume only decreases by 8% when CdS was converted to Cu 2 S, and therefore, the morphology and size of nanorods were well preserved after the cation exchange. Similar structures have been obtained in CdTe/Cu 2-x Te 44 and CdSe/ PbSe [99] systems.…”
Section: D Linear Heterostructuressupporting
confidence: 83%
“…17,18,33 The Drude dielectric constant  Drude (, as a function of the frequency , has the form: Several recent papers have shown that the Drude model provides a reliable description of semiconductor nanocrystals with mobile carriers.…”
Section: Microwave-assisted Synthesis and Characterization Of Covellimentioning
confidence: 99%
“…2 Nanoscale cation exchange provides control over the spatial arrangement of different phases within nanocrystals, allowing for the synthesis of heterostructures with tunable properties. [26][27][28] Cation exchange therefore can be an important tool for controlling the plasmonic properties of semiconductor nanocrystals that combines the spatial resolution of top-down fabrication techniques with the high throughput of solution-based syntheses. The use of cation exchange to modify the optical properties of metal chalcogenides nanocrystals remains a novel field of inquiry.…”
Section: Introductionmentioning
confidence: 99%